Effect of Folic Acid Food Fortification in Canada on Congenital Heart Disease Subtypes. Issue 9 (30th August 2016) - Liu, Shiliang; Joseph, K.S.; Luo, Wei; León, Juan Andrés; Lisonkova, Sarka; Van den Hof, Michiel; Evans, Jane; Lim, Ken; Little, Julian; Sauve, Reg; Kramer, Michael S.
Abstract : Background: Previous studies have yielded inconsistent results for the effects of periconceptional multivitamins containing folic acid and of folic acid food fortification on congenital heart defects (CHDs). Methods: We carried out a population-based cohort study (N=5 901 701) of all live births and stillbirths (including late-pregnancy terminations) delivered at ≥20 weeks' gestation in Canada (except Québec and Manitoba) from 1990 to 2011. CHD cases were diagnosed at birth and in infancy (n=72 591). We compared prevalence rates and temporal trends in CHD subtypes before and after 1998 (the year that fortification was mandated). An ecological study based on 22 calendar years, 14 geographic areas, and Poisson regression analysis was used to quantify the effect of folic acid food fortification on nonchromosomal CHD subtypes (n=66 980) after controlling for changes in maternal age, prepregnancy diabetes mellitus, preterm preeclampsia, multiple birth, and termination of pregnancy. Results: The overall birth prevalence rate of CHDs was 12.3 per 1000 total births. Rates of most CHD subtypes decreased between 1990 and 2011 except for atrial septal defects, which increased significantly. Folic acid food fortification was associated with lower rates of conotruncal defects (adjusted rate ratio [aRR], 0.73, 95% confidence interval [CI], 0.62–0.85), coarctation of the aorta (aRR, 0.77; 95% CI, 0.61–0.96), ventricular septal defects (aRR, 0.85; 95% CI, 0.75–0.96), and atrial septal defects (aRR, 0.82; 95% CI, 0.69–0.95) but not severe nonconotruncal heart defects (aRR, 0.81; 95% CI, 0.65–1.03) and other heart or circulatory system abnormalities (aRR, 0.98; 95% CI, 0.89–1.11). ConclusionS: The association between food fortification with folic acid and a reduction in the birth prevalence of specific CHDs provides modest evidence for additional benefit from this intervention. Abstract : Supplemental Digital Content is available in the text.